Synthesis of Oligosuccinimide and Evaluation of Its Corrosion Inhibition Performance on Carbon Steel in CO2-Saturated 1% NaCl Solution - Muhamad Jalil Baari; Bunbun Bundjali; Deana Wahyuningrum (Institute for Research and Community Services (LPPM) ITB, 2020)
Oligosuccinimide (OSI) is an oligomer with several repeating units of succinimide. In this study, OSI was synthesized by thermal condensation between maleic anhydride and ammonium carbonate. The chemical structure of the synthesized compound was confirmed by FTIR and NMR spectroscopy as well as LC-MS characterization. Evaluation of its performance as corrosion inhibitor and the adsorption mechanism on a carbon steel surface in CO2-saturated 1% (w/v) NaCl solution was performed using electrochemical techniques (electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization) and weight-loss methods. These tests were simultaneously carried out for all fractions without separation. The EIS results showed that the inhibition efficiency (IE) of the OSI increased with increasing concentration but decreased at higher temperatures. The potentiodynamic polarization data indicated that the OSI acted as a mixed inhibitor. Adsorption of OSI on the carbon steel generally obeys the Langmuir adsorption isotherm according to curve linearity, which relates the degree of surface coverage to the inhibitor concentration. The standard Gibbs free energy of the adsorption values (âˆ†G° ads) were negative within the range of -33.14 to -38.73 kJ.mol-1, which indicates the spontaneity of the adsorption process on the carbon steel surface and that OSI molecules interacted with the carbon steel through semi-physisorption.